Prevalence and quantification of thermophilic Campylobacter spp. in Italian retail poultry meat: Analysis of influencing factors. (April 2017) - Stella, Simone; Soncini, Gabriella; Ziino, Graziella; Panebianco, Antonio; Pedonese, Francesca; Nuvoloni, Roberta; Di Giannatale, Elisabetta; Colavita, Giampaolo; Alberghini, Leonardo; Giaccone, Valerio
Abstract: Retail poultry meat is a crucial vehicle for consumers' exposure to Campylobacters, but no official controls are currently applied in Italy. The aim of this study was the evaluation of Campylobacter contamination of a wide range of poultry meats marketed in Italy. N. 472 chicken and turkey meat samples (sectioned meats, offal, meat preparations and products) were taken from slaughterhouses, deboning plants and different retailers and submitted to detection/enumeration of Campylobacter spp. The isolates were identified by phenotypic and biomolecular techniques. Campylobacter spp. was detected in 34.1% of the samples, with general low counts. Higher values were observed in offal (especially liver) and sectioned meats, with significantly higher rates in skin-on samples (86.8% vs 32.7%). Minced meat preparations showed lower prevalence (22.4% vs 58.3%) and counts than whole pieces. Decreasing rates were observed among slaughterhouses (80%), deboning plants (49%), butcher's shops (37%) and large scale retailers (25%). Sectioned chicken meats were significantly more contaminated than turkey meats. Almost all the isolates were identified as C. jejuni or C. coli, with similar prevalences (18.4% and 20.5%, respectively); C. jejuni was predominant only in samples from slaughterhouses/deboning plants. For setting future control programs, meat typology should be considered the main critical factor. Highlights: Italian retail poultry meats are frequently contaminated by Campylobacter spp. High Campylobacter numbers were mostly present on poultry offal. Decreasing Campylobacter rates are detectable along the marketing chain. Meat typology is the main factor influencing the Campylobacter contamination.